Essential Oil Composition of Five Thymus Species from Bulgaria. Issue 10 (15th September 2021) - Trendafilova, Antoaneta; Todorova, Milka; Ivanova, Victoria; Zhelev, Petar; Aneva, Ina
Abstract: In this study, the essential oil composition of five Thymus species, belonging to Sect. Hyphodromi (A. Kerner) Halácsy – Thymus atticus Čelak., T. leucotrichus Halácsy, T. striatus Vahl, T. zygioides Griseb. and T. perinicus (Velen.) Jalas. was studied by GC/MS/FID. T. atticus, T. leucotrichus, and T. striatus were characterized by high amounts of sesquiterpenoids (57.7, 78.9 and 79.7 %, respectively) with β‐caryophyllene and caryophyllene oxide as the main constituents. Aromatic compounds (61.2 %) were the most abundant group in T. zygioides essential oil, with thymol (51.2 %) as the principal component. The essential oil from the endemic species T. perinicus contained almost equal amounts of monoterpenoids (37.8 %) and aromatic compounds (36.0 %) with borneol (17.9 %) and thymol (20.9 %) as the major components. The obtained results revealed the existence of new chemotypes of T. atticus (caryophyllene oxide/β‐caryophyllene), T. leucotrichus (β‐caryophyllene/elemol/germacrene D) and T. striatus (β‐caryophyllene/germacrene D/caryophyllene oxide). The essential oil content of endemic T. perinicus is reported for the first time. Principal component analysis (PCA) and cluster analysis (CA) were used to investigate the variations in the essential oils of different Thymus species from Sect. Hyphodromi (A. Kerner) Halácsy. Abstract :